MAKTABGACHA VA BOSHLANG’ICH TA’LIM SIFATI VA SAMARADORLIGINI OSHIRISHNING TENDENSIYALARI - Valiyeva Mamlakatxon Muhammadjon qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In recent years, there has been a growing emphasis on enhancing the quality and efficacy of pre-school and primary education. This paper examines current trends in this area, including the adoption of innovative teaching methods, curriculum updates, and the integration of technology. The study also discusses the impact of these improvements on student learning outcomes.